Dada a função f(x) = 3x - 2, o valor de f (-1) + f(2) - f (3) é:?
Soluções para a tarefa
Respondido por
1
colocamos -1, 2 e 3 no lugar de x:
f(x)=3x-2
f(-1)=3(-1)-2=-3-2=-5
f(2)=3(2)-2=6-2=4
f(3)=3(3)-2=9-2=7
-5+4-7=-8
f(x)=3x-2
f(-1)=3(-1)-2=-3-2=-5
f(2)=3(2)-2=6-2=4
f(3)=3(3)-2=9-2=7
-5+4-7=-8
Respondido por
0
f de -1 = -5
f de 2 = 4
f de 3 = 7
- 5 + 4 - 7 = - 8
f de 2 = 4
f de 3 = 7
- 5 + 4 - 7 = - 8
Perguntas interessantes
Química,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás
Química,
1 ano atrás
Matemática,
1 ano atrás
Biologia,
1 ano atrás